THE IMPACT OF CUSTOMER FOCUS, OBSESSION ON QUALITY, EDUCATION AND TRAINING, TEAMWORK AND CONTINUOUS IMPROVEMENT ON PRODUCT QUALITY - PUTRI, ERVINA ANGGRAINI (INDONESIAN RESEARCH SOCIETY, 2019)
The purpose of this study is to study the direct and indirect interactions between CustomerFocus, Education and Training, Team Cooperation, and Continuous Improvement ofProduct Quality. The study was carried out in the Small and Medium Industry soun noodlesin Klaten Regency. The subjects of this study were the owners of Small and MediumIndustries soun noodles.This study has a contribution, especially in explaining themechanism to provide educational programs and job training for employees to continue toimprove their skills and work skills, build strong teamwork supported by high morale andcontinuously develop and diversify products based on customer demand, feedback betweencustomers, quality of competitors, and ways employee work.